PERILAKU MENYIMPANG DI KALANGAN SISWA (STUDI DI SEKOLAH DASAR NEGERI 4 TENGGULI KECAMATAN SAJAD) TAHUN PELAJARAN 2023-2024 - Anjeli Anjeli; Suhari Suhari; Muspian Muspian (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This journal aims to describe and analyze deviant behavior carried out by students in classes IV A and V A as well as the efforts made by teachers to overcome student deviant behavior at Tengguli 4 Elementary School, Sajad District. This research uses a qualitative research approach with a descriptive research type. Data collection techniques in this research used interview, observation and documentation techniques. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Data validity checking techniques use source triangulation, technical triangulation and member checks. The results of this research show that: 1. Deviant behavior carried out by students in classes IV A and V A at State Elementary School 4 Tengguli, Sajad District in the form of: Making noise, dressing sloppy, saying dirty things, taking friends' things, asking for money by force. 2. Efforts made by teachers to overcome student deviant behavior at Tengguli 4 State Elementary School, namely preventive action through extracurricular scout activities, Monday ceremonies, Al-Quran reading activities, congregational prayers, and providing discipline to students. The two curative actions are by providing advice, direction, guidance, approaches to students, and giving special attention to students who have problems. Repressive efforts here include giving sanctions to students in the form of cleaning, additional assignments, as well as warning letters and letters of appeal to parents.